Lithium phosphide/lithium chloride coating on lithium for advanced lithium metal anode. Issue 32 (2nd August 2018) - Lin, Liangdong; Liang, Feng; Zhang, Kaiyuan; Mao, Hongzhi; Yang, Jian; Qian, Yitai
Abstract : Lithium metal has been regarded as an ideal anode material for high-energy-density batteries. Abstract : Lithium metal has been regarded as an ideal anode material for high-energy-density batteries. However, its high chemical reactivity, virtually infinite volume change and dendrite growth greatly reduce coulombic efficiency and increase potential safety hazards, thereby limiting its practical performance. Here, Li3 P/LiCl-coated Li was successfully prepared by a simple reaction between PCl3 and Li at room temperature. Li3 P, as a Li-ion conductor, reduces interface impedance and improves the electrochemical kinetics. LiCl, as the minor phase, enhances Li diffusion at the interfaces and reinforces the Li metal protection together with Li3 P, suppressing the formation of Li dendrites. Thus, cycle stability and rate capability are greatly improved, as demonstrated both in symmetric cells and in the Li//LiCoO2 and Li//S full cells.